2003
DOI: 10.1007/s00784-003-0233-4
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomas of the oral and maxillofacial region: a review of 32 cases in 25�years

Abstract: Thirty-two cases of sarcomas involving the oral and maxillofacial region over a period of 25 years were reviewed. The age range was from 5 months to 77 years with a mean age of 42. The male to female ratio was 3:1. The sarcomas were located in the maxilla including the maxillary sinus (n= 13), mandible (n= 13), buccal mucosa (n= 3), temporomandibular fossa (n= 2), and submandibular region (n= 1). Histologically sarcomas were classified as osteosarcoma (n= 9), malignant fibrous histiocytoma (n= 7), rhabdomyosar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 12 publications
7
90
2
3
Order By: Relevance
“…Head and neck sarcomas are extremely rare malignancies and they make about 4% -10% of all sarcomas (27). Oral sarcomas show male preponderance with the average age of 42 years (28).…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck sarcomas are extremely rare malignancies and they make about 4% -10% of all sarcomas (27). Oral sarcomas show male preponderance with the average age of 42 years (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of 201 patients with craniofacial osteosarcoma Smeele et al (8) have reported improved survival with complete resection and adjuvant chemotherapy. Early radical resection was also recommended as the primary treatment with the aim of local control in two recent series of patients with head and neck sarcomas especially located in the maxillofacial region (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Both rhabdomyosarcoma patients developed distant lung metastasis and succumbed to their disease within 2 years of their first visits. In a review of sarcomas of the oral and maxillofacial region, Yamaguchi et al (20) reported that 3 of 5 rhabdomyosarcoma cases died within 3 years after treatment and that distant metastasis occurred in the deceased but not in the surviving and disease-free patients. These observations strongly indicate that distant metastasis is a major complication contributing to the poor outcome in patients with rhabdomyosarcoma and malignant melanoma.…”
Section: Distant Metastasis -----------------------------------Clinicmentioning
confidence: 99%